2014
DOI: 10.1155/2014/541232
|View full text |Cite
|
Sign up to set email alerts
|

Garage Location Selection for Public Transportation System in Istanbul: An Integrated Fuzzy AHP and Fuzzy Axiomatic Design Based Approach

Abstract: We try to determine the best location for a bus garage, in which maintenance and repair activities are operated, for public transportation system in Istanbul. An integrated multicriteria decision making technique (MCDM) is used to obtain reliable results. Firstly, various criteria related to garage location selection are specified and weighted by fuzzy AHP (analytical hierarchy process). Then, these weights are used in fuzzy axiomatic design (AD) technique to determine the precedencies of the alternative garag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…To convert these data into numerical data, the membership functions of given linguistic variables showed in Figure 5 are used. According to this data; if a supplier is expressed as "very poor" it gets (0, 0, 6) value, if it is expressed as "poor" it gets (3,7,11) value, if it is expressed as "fair" it gets (8,12,16) value, if it is expressed as "good" it gets (13,17,21) value and if it is expressed as "very good" it gets (18,25,25) value.…”
Section: The Application Of Fuzzy Ad Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…To convert these data into numerical data, the membership functions of given linguistic variables showed in Figure 5 are used. According to this data; if a supplier is expressed as "very poor" it gets (0, 0, 6) value, if it is expressed as "poor" it gets (3,7,11) value, if it is expressed as "fair" it gets (8,12,16) value, if it is expressed as "good" it gets (13,17,21) value and if it is expressed as "very good" it gets (18,25,25) value.…”
Section: The Application Of Fuzzy Ad Approachmentioning
confidence: 99%
“…Besides they claimed that Fuzzy AD approach could be helpful in green supplier selection and subjects like production optimization. Bilisik et al [18] investigated a location selection problem where maintenance and repair processes to be executed for Istanbul's mass transit system. In this study, criteria weights determined by Fuzzy AHP are used inside Fuzzy AD and alternative garage location priorities are identified.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that ten research papers did not use consistency check, five used it and showed the results. One research paper explains that consistency check for their research was not needed [34]. Eight from 19 research papers used defuzzification for changing fuzzy into crisp numbers.…”
Section: Transport Technology 53%mentioning
confidence: 99%
“…Tab. 10 shows that there is quite a wide variation of the use of FAHP in urban mobility system, from customer satisfaction [34,35], infrastructure projects [30,37,38,36], treatment of uncertainties [29] to environment impact evaluations [5,4].…”
Section: Transport Technology 53%mentioning
confidence: 99%
“…For this, the methodology of the fuzzy analytic hierarchy process (AHP) implemented by Buckley (1985) was employed. Fuzzy AHPs have been applied across a range of fields, including construction (Hsieh et al 2004;Jaskowski et al 2010), education (Goksu 2008;Celik, Kandakoglu, & Er 2009), human resources (Chou et al 2012), location selection (Bilisik et al 2014), marine engineering (Miri Lavasani et al 2011;Wang & Chin 2011;Celik & Kandakoglu 2012;Yanar & Tozan 2012), the automotive industry (Nepal et al 2010;Badizadeh & Khanmohammadi 2011;Bilgen & Sen 2012;Ghadimi et al 2012;Rathi et al 2015), supplier selection (Chan et al 2008;Kilincci & Onal 2011;Yucenur et al 2011;Shaw et al 2012;Rezaei et al 2014) and technology management (Erensal et al 2006). A comprehensive description of the methodology is expounded in the next section.…”
Section: Introductionmentioning
confidence: 99%